Fatty liver and cytokines - Pirinen, Julia (My University, 2023)
Non-alcoholic fatty liver is the most common liver disease worldwide with the prevalence of around 25% in adult population. Comorbidities of non-alcoholic fatty liver include type 2 diabetes, metabolic syndrome, cardiovascular diseases, and chronic liver diseases. In addition, fatty liver can in some cases develop into non-alcoholic steatohepatitis or cirrhosis, later of which predisposes a patient to hepatocellular carcinoma. Cytokines, small proteins acting on communications and interactions between cells, are known to predict the development of insulin resistance and play a crucial role in many metabolic diseases. Under normal physiologic conditions hepatic cytokine production is minimal or absent whereas hepatic cells produce inflammatory cytokines as a result to pathological stimuli. There is not yet a clinical serum marker for the prediction or diagnosis of non- alcoholic fatty liver and most of the previous studies and publications have concentrated more on cytokines’ associations to non-alcoholic steatohepatitis than simple steatosis. This thesis includes a review of literature on the subject which cytokines are associated to liver steatosis and an analysis based on Young Finns Study (YFS) data on cytokines’ association to later fatty liver. YFS is a large population-based follow-up study about the determinants of cardiovascular risk factors from childhood into adulthood. Regarding of the subject of this thesis, a study population of 2130 participants were measured for 48 cytokine, chemokine, and growth factor concentrations and four years later 2042 of the subjects were examined for liver steatosis using liver ultrasound imaging. The association between cytokine concentrations and liver steatosis four years later was studied on a statistical analysis using Spearman’s correlation test and logistic regression analysis with confounding factors including age, body mass index, smoking status, alanine-aminotransferase (ALT), LDL cholesterol and total cholesterol. Men and women were analyzed separately. The results of the study indicate that higher serum interleukin-18 and hepatocyte growth factor (HGF) serum levels predict fatty liver in women. Higher serum ALT concentrations were also associated to later fatty liver in men. In the review of literature part of the thesis several cytokines, including TNF-α, IL-1, IL-6, IL-10, IL-17, and members of the CC and CXC family were found to be associated to non-alcoholic fatty liver disease progression. Interleukin-18 and hepatocyte growth factor were not included in these previous findings. Hepatocyte growth factor has been earlier studied only in rodent models of fatty liver and the association has been protective against liver steatosis, making this a novel finding. Further research is needed to determine if either of these cytokines could have clinical relevance in prediction of fatty liver in the future.
Keywords: fatty liver, non-alcoholic fatty liver, hepatic steatosis, cytokine, interleukin, Cardiovascular Risk in Young Finns Study